Coaching for Performance Management: The Role of Motivation and Commitment in the Workplace - Haryanto, Budi (IJOSMAS, 2021)
This study investigates whether increased attention paid to coaching practices affects employee intrinsic motivation, work commitment, and individual performance. Data were collected from 143 employees of the private manufacturing industry in Tangerang using quantitative methods and confirmatory surveys. This study shows that coaching has a positive and significant effect on intrinsic motivation, work commitment, and employee performance. The results of this study could have significant implications for HR managerial decision-making regarding the coaching practice process in the manufacturing industry employees in Indonesia. This study also helps the HR management of the manufacturing industry to seriously assess their HR development investment plans in the form of coaching practices and direct their company's HR strategic planning.